Menjelajahi Ilmu Manajemen Generasi Ke 5 (Brainware Management) Menuju Kualitas Ilmu Manajemen Terintegrasi Dengan Posmodernisme - Adang Adang; Dedi Hadian (Majalah Bisnis & IPTEK, 2018)
The age of postmodernism is part of the rejection of the paradigm of Rene Descrates through Cartesian - Newtonian jargon. This region rarely gets attention in the field of science / management flow in Indonesia. The conceptualization of management science in Indonesia tends to be quantified by statistical and mathematical formulas. The pioneers of this science forget Peter Drucker who introduced the "Heart Management" long ago, forgetting David Boje with the cycle of management postmodernism. The shallowness of the reasoning of Indonesian scientists about the management of postmodernism, may be the biggest consequence of postmodernist education on mere positivisation of science. So that intelligence is built is intelligence that has been structured due to technological progress, what happens. The author's research reveals more corruptors, intelligence is increasingly systematized, so that the mindset of a management scientist is merely moving without recognizing integrated reasoning.